Nanotecnologia aplicada ao concreto: efeito da mistura física de nanotubos de carbono em matrizes de cimento Portland: efeito da mistura física de nanotubos de carbono em matrizes de cimento Portland - Valquiria Silva Melo (2009)
Nanotechnology has brought significant innovations in science and engineering. A recent development in this field is carbon nanotubes. Carbon nanotubes are cylinders formed by layers of carbon, which can be built with one layer single wall carbon nanotubes or several ones multiple wall carbon nanotubes. The objective of this study is to analyze the behavior of Portland cement matrices built with the physical mixture of surface-treated multi-walled carbon nanotubes. Different types of chemical admixtures were used in batching the mortars. Three carbon nanotubes cement ratios were employed: 0.30, 0.50 and 0.75%. The mortar mechanical properties evaluated were the compressive strength, the splitting tensile strength and the secant modulus of elasticity. Scanning electron microscopy, helium picnometry and specific surface area test were used in the microstructure analysis. The test results showed significant better mechanical properties and microstructure of the mortar with 0.30% of carbon nanotubes.